2013
DOI: 10.1155/2013/907209
|View full text |Cite
|
Sign up to set email alerts
|

Wound-Healing Potential of Cultured Epidermal Sheets Is Unaltered after Lyophilization: A Preclinical Study in Comparison to Cryopreserved CES

Abstract: Lyophilized Cultured Epidermal Sheets (L-CES) have been reported to be as effective as the cryopreserved CES (F-CES) in treating skin ulcers. However, unlike F-CES, no preclinical study assessing wound-healing effects has been conducted for L-CES. The present study was set out to investigate the microstructure, cytokine profile, and wound-healing effects of L-CES in comparison to those of F-CES. Keratinocytes were cultured to prepare CES, followed by cryopreservation at −70°C and lyophilization. Under microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…However, if living cells are necessary to promote wound healing, the result of this study has no consistency. Biologically active substances stored in the keratinocytes, such as interleukin-1, vascular endothelial growth factor, and transforming growth factor-α, may be released from the keratinocytes regardless of cell viability and may contribute to wound healing [26]. Besides, some authors have mentioned that the membrane structure of the CE contributes to creating a comfortable environment for recipient cells in the wound bed to proliferate and migrate [17,20].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…However, if living cells are necessary to promote wound healing, the result of this study has no consistency. Biologically active substances stored in the keratinocytes, such as interleukin-1, vascular endothelial growth factor, and transforming growth factor-α, may be released from the keratinocytes regardless of cell viability and may contribute to wound healing [26]. Besides, some authors have mentioned that the membrane structure of the CE contributes to creating a comfortable environment for recipient cells in the wound bed to proliferate and migrate [17,20].…”
Section: Plos Onementioning
confidence: 99%
“…For example, lyophilized CEs may be a suitable wound dressing, given its long storage period at room temperature. In fact, Jang et al reported that lyophilized CEs accelerated wound healing at the same level as cryopreserved CEs [26]. Besides, CEs sterilized by gamma irradiation would have less probability of contamination (e.g., with bacteria and viruses) to be a much safer product.…”
Section: Plos Onementioning
confidence: 99%
“…Therefore, by combining in vivo and in vitro experiments, we revealed that Rd activated the cAMP/PKA signaling pathway to enhance adaptive thermogenesis in Rd‐treated HFD mice. In addition, a previous study found that Rd, the most abundant active ingredient in ginseng leaves, increased cAMP levels in keratinocytes to activate Creb and promote skin regeneration . Although we found that Rd also increased cAMP levels in brown adipocytes, the molecular mechanisms by which it achieves this requires further study.…”
Section: Discussionmentioning
confidence: 45%
“…Ginsenosides as the main active ingredient of ginseng can be classified into protopanaxadiol (PPD) and protopanaxatriol groups according to the position of the sugar moieties at carbon‐3 and ‐6 . Ginsenoside Rd, a PPD‐type compound, is regarded as one of the major active components in ginseng leaves . It has been reported that Rd exhibits some pharmacological effects, including protective effects against transient focal cerebral ischemia and apoptosis induced by glutamate in neurons, protective effects against tumors and inflammation in many kinds of diseases such as colitis and Alzheimer disease, and an inhibitory effect on the formation of reactive oxygen species in cells.…”
Section: Introductionmentioning
confidence: 99%
“…Human mucosal epithelial cells were serially cultured for the skin epithelial sheets, following a previously described method (Rheinwald and Green, , ; Jang et al , ) with modifications. Briefly, the mucosal epithelial cells were co‐cultured on lethally irradiated 3T3 murine fibroblasts to form cell sheets, with or without fibrin, for 10 days.…”
Section: Methodsmentioning
confidence: 99%